2004
DOI: 10.1002/cite.200403415
|View full text |Cite
|
Sign up to set email alerts
|

Elektrochemische Mikrodurchflussanordnung für Standardexperimente im Studium

Abstract: No abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…Liauw et al described a miniaturized enzyme membrane reactor [5] and published a report about a lecture with subsequent practical training course [6]. Köhler et al reported about a reaction/diffusion experiment and electrochemical experiments [7] using low cost microchannels made of plastic tape [8]. Procedural basic experiments were not considered in greater detail yet.…”
Section: Introductionmentioning
confidence: 97%
“…Liauw et al described a miniaturized enzyme membrane reactor [5] and published a report about a lecture with subsequent practical training course [6]. Köhler et al reported about a reaction/diffusion experiment and electrochemical experiments [7] using low cost microchannels made of plastic tape [8]. Procedural basic experiments were not considered in greater detail yet.…”
Section: Introductionmentioning
confidence: 97%
“…Eine aktuelle Übersicht zu laufenden nationalen und internationalen Aktivitäten haben Liauw und Treu zusammengestellt [3]. Zu den deutschen Hochschulen, die die Integration mikroverfahrenstechnischer Inhalte in die Lehre seit einigen Jahren vorantreiben, gehören unter anderem die RWTH Aachen [2,3], die FriedrichSchiller-Universität Jena [4 -6] und die TU Ilmenau [7]. Von der DECHEMA wird seit 2003 ein entsprechender Weiterbildungskurs angeboten [8].…”
Section: Introductionunclassified